Species authentication of thermally processed meat and meat products by proteomics approach - Zainal Abidin, Siti Aimi Sarah (2014)
The present study focused on the development of a protein-based method which could differentiate pork from beef, chevon and chicken meat. Current protein-based detection methods such as ELISA and western blot have been extensively used for such species determination. However, heating of meat brings extensive changes in target antigen appearance and contributes to false detection. Hence, species authentication using proteomics approach was chosen as this state-of-the-art technology offers high discriminating power, specificity and selectivity, while the detection could be carried out on denatured protein. The purpose of this study was to determine porcine-specific peptide biomarker from thermally processed meat using combination of two-dimensional gel electrophoresis (2-DE) and mass spectrometry approach. In the initial phase, proteome extract of raw and cooked pork were profiled using two-dimensional gel electrophoresis to screen for thermally stable proteins available in the meat which has been subjected to 3 different heat regimes (1) chilled at 4°C, (2) boiled at 100 °C for 30 min and (3) autoclaved at 121°C, 15 psi for 20 min. Following to that, all thermal stable protein spots were identified using the MALDI-TOF-MS. In the second phase, selection of porcine-specific peptide was carried out using bioinformatics tool (CLUSTAL W and MS-Digest) and followed by a verification using the LC-QTOF-MS. In the final phase, the porcine-specific peptides were tested and verified on commercial meat products using the multiple reactions monitoring (LC-ESI-QQQ-MS). The 2-DE separations of autoclaved pork samples revealed only 43 spots in the gel, in which their presence and minimal changes following the thermal treatment confirmed that these spots are less susceptible to heat based on its high abundance in muscle. The aforementioned 43 spots were then compared with spots from the gel images of other species (cattle, goats and chickens). Prominent molecular weight differences were observed among the species studied, while no differences in isoelectric points were noted among the meat species. Through the protein identification of heat treated meat using MALDI-TOF/TOF mass spectrometry, only 13 proteins were consistently detected and found to be thermally stable throughout the treatment. Subsequently, interspecies comparison of amino acid sequence for each protein was carried out to search for porcine-specific peptides. The bioinformatics analysis revealed 35 potential peptides which are unique to pork only. However, a thorough investigation of LC-QTOF-MS data presented that only seven porcine-specific peptides were consistently detected by the mass spectrometry system. Specifically, two peptides were found to be derived from lactate dehydrogenase, one from creatine kinase, and four from serum albumin protein. Then, the multiple reactions monitoring method was established for verification whereby only four of the peptides biomarkers were detected in commercial meat samples. Peptides EVTEFAK, LVVITAGAR, FVIER and TVLGNFAAFVQK were found to be consistently detected in the commercial meat products and displayed species-specific properties. In conclusion, meat species authentication through the combined platforms of 2DE and mass spectrometry is highly potential to offer scientifically valid and reliable results even at peptide level. Besides, the specificity and selectivity offered by the proteomics approach also provide a robust platform for halal authentication of thermally processed meat and meat products.